2014
DOI: 10.1111/jvp.12101
|View full text |Cite
|
Sign up to set email alerts
|

Oclacitinib (APOQUEL®) is a novel Janus kinase inhibitor with activity against cytokines involved in allergy

Abstract: Janus kinase (JAK) enzymes are involved in cell signaling pathways activated by various cytokines dysregulated in allergy. The objective of this study was to determine whether the novel JAK inhibitor oclacitinib could reduce the activity of cytokines implicated in canine allergic skin disease. Using isolated enzyme systems and in vitro human or canine cell models, potency and selectivity of oclacitinib was determined against JAK family members and cytokines that trigger JAK activation in cells. Oclacitinib inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
205
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(224 citation statements)
references
References 19 publications
(26 reference statements)
3
205
0
4
Order By: Relevance
“…We found that mice treated orally with JAK inhibitors showed a significant decrease in scratching behavior; however, ear thickness was not significantly reduced. Our itching results are supported for oclacitinib by the recently published clinical study in dogs (Gonzales et al, 2014). For tofacitinib, Fujii and Sengoku (2013) reported an anti-inflammatory effect in the oxazolone-induced chronic dermatitis model in rats (effects on itch were not reported).…”
Section: Availability Of Jak Inhibitors On Allergic Dermatitissupporting
confidence: 81%
See 3 more Smart Citations
“…We found that mice treated orally with JAK inhibitors showed a significant decrease in scratching behavior; however, ear thickness was not significantly reduced. Our itching results are supported for oclacitinib by the recently published clinical study in dogs (Gonzales et al, 2014). For tofacitinib, Fujii and Sengoku (2013) reported an anti-inflammatory effect in the oxazolone-induced chronic dermatitis model in rats (effects on itch were not reported).…”
Section: Availability Of Jak Inhibitors On Allergic Dermatitissupporting
confidence: 81%
“…Nonetheless, there are still limited options and classic topical corticosteroids remain the primary foundation of topical treatment, with topical calcineurin inhibitors preferred for treatment of the face and intertriginous areas (Ring et al, 2012). To open up the option of therapeutic agents for allergic skin disorders, we focused on the Janus kinase (JAK) inhibitors, which have been recently developed for rheumatoid arthritis and pruritic inflammatory skin diseases (Cosgrove et al, 2013a,b;Fujii and Sengoku, 2013;Ports et al, 2013;Gonzales et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oclacitinib (APOQUEL®) is a novel Janus kinase (JAK) inhibitor that has been shown to inhibit cytokines involved in pruritus (IL-31) and allergy and inflammation (IL-2, IL-4, IL-6 and IL-13) [12]. Oclacitinib is currently approved for the control of pruritus associated with allergic dermatitis and for the control of atopic dermatitis in dogs that are at least 12 months of age [13].…”
Section: Open Accessmentioning
confidence: 99%